Flash site workshop - Milburn, Ken, 1935-; OnCall Interactive; Flash Site Workshop Team. (Indianapolis, Indiana : Sams Pub., 2001)
1. Computer graphics. 2. Flash (Computer file).
Includes index.
Includes bibliographical references (p. [329]-341) and index.
Basic ed. students
Keywords: Flash (Computer file); Computer graphics; Computer animation; Web sites -- Design